2023
DOI: 10.3389/fonc.2023.1199608
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis to identify a novel diagnostic marker of lung adenocarcinoma and its immune infiltration landscape

Abstract: BackgroundLung cancer continues to be a problem faced by all of humanity. It is the cancer with the highest morbidity and mortality in the world, and the most common histological type of lung cancer is lung adenocarcinoma (LUAD), accounting for about 40% of lung malignant tumors. This study was conducted to discuss and explore the immune-related biomarkers and pathways during the development and progression of LUAD and their relationship with immunocyte infiltration.MethodsThe cohorts of data used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It is well known that the immune system plays a role in the development of lung cancer and the prognostic process. In the study by Zhu et al (2023) , the immune infiltration of LUAD was investigated. It was found that 12 hub genes, including HBA2 , may be involved in LUAD progression via immune-related signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the immune system plays a role in the development of lung cancer and the prognostic process. In the study by Zhu et al (2023) , the immune infiltration of LUAD was investigated. It was found that 12 hub genes, including HBA2 , may be involved in LUAD progression via immune-related signaling pathways.…”
Section: Discussionmentioning
confidence: 99%